2022
DOI: 10.1101/2022.09.07.506901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglia protect fungi against copper starvation and promote brain infection

Abstract: Microglia provide protection against a range of brain infections, but how these glial cells respond to fungi is poorly understood. We investigated the role of microglia in the context of cryptococcal meningitis, the most common cause of fungal brain infections in humans. Using a series of transgenic- and chemical-based microglia depletion methods we found that, contrary to their protective role during other infections, microglia supported cryptococcal fungal brain infection. We show that microglia become hosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…In the current work, we used an intranasal infection model where yeast infection disseminates from the lung to other organs following breakdown of pulmonary barrier immunity. We found that loss of microglia in the CNS equated to reduced fungal brain infection, validating our earlier observations in the acute infection model [21]. However, further examination of PLX5622-treated mice revealed that fungal infection was also reduced in the lung, which may have exaggerated the reduced fungal brain burden by reducing the rate of extrapulmonary dissemination.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the current work, we used an intranasal infection model where yeast infection disseminates from the lung to other organs following breakdown of pulmonary barrier immunity. We found that loss of microglia in the CNS equated to reduced fungal brain infection, validating our earlier observations in the acute infection model [21]. However, further examination of PLX5622-treated mice revealed that fungal infection was also reduced in the lung, which may have exaggerated the reduced fungal brain burden by reducing the rate of extrapulmonary dissemination.…”
Section: Discussionsupporting
confidence: 88%
“…We recently showed that microglia support C. neoformans brain infection by acting as a fungal reservoir during acute meningitis (intravenous infection) [21]. Loss of microglia in the PLX5622-treated mice may therefore cause a reduction in brain fungal burdens by removing this growth niche, in addition to reduced extrapulmonary dissemination from the lung, or the loss of microglia independently reduces brain fungal burden (as we previously observed in the intravenous infection model).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations